Hepatic hydrothorax without ascites - Z, Bitar; Hb, Fayed; EE, Al-Hamer; H, Hafiz (IIUM Medical Journal Malaysia, 2008)
Hepatic hydrothorax (HH) in the absence of ascites is a rare complication of liver cirrhosis. A 58-year-old woman presented to our department with dyspnea because of massive right pleural effusion requiring chest tube drainage. Investigations confirmed chronic hepatitis C, She had no signs of hepatic failure or ascites but there was evidence of portal hypertension. After pleural drainage and standard treatment for ascites with restriction of salt intake and diuretic administration, the pleural effusion improved with minimal recurrence.